2011
DOI: 10.1007/s11144-011-0308-1
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of substituents upon the hydrogenation of nitrobenzene using a polymer-supported palladium-imidazole complex catalyst

Abstract: Hydrogenation of various nitroarenes by a polymer-supported palladium-imidazole complex at ambient conditions was investigated. The effect of various substituents upon the rate of hydrogenation of nitrobenzene was studied. The rate of para-substituted nitrobenzene hydrogenation was related to the corresponding Hammett substituent constant. The kinetics of hydrogenation and the reusability of the catalyst were also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Dimethylformamide and dimethyl sulphoxide, although polar, may coordinate strongly with the catalyst and so hinder coordination of hydrogen and/or olefin with the catalyst, resulting in low reaction rate. The higher solubility of hydrogen in methanol as compared to DMF and DMSO would also enhance the rate [30,31]. Hence, methanol was used as solvent for the hydrogenation of olefins and also for nitro compounds and Schiff bases ( Table 3).…”
Section: Kinetics Of the Hydrogenation Of Olefinsmentioning
confidence: 99%
“…Dimethylformamide and dimethyl sulphoxide, although polar, may coordinate strongly with the catalyst and so hinder coordination of hydrogen and/or olefin with the catalyst, resulting in low reaction rate. The higher solubility of hydrogen in methanol as compared to DMF and DMSO would also enhance the rate [30,31]. Hence, methanol was used as solvent for the hydrogenation of olefins and also for nitro compounds and Schiff bases ( Table 3).…”
Section: Kinetics Of the Hydrogenation Of Olefinsmentioning
confidence: 99%
“…Linear correlation with a slope of 0.98 is clearly observed, which means that the activation process occurs on the surface of the catalyst and is sensitive to substituents. Former researches on various substituents effect in nitroaromatics to aminoaromatics reaction reported that both similar and opposite trends exist for different catalyst systems, which indicates that the effects from substituents are strongly determined by the catalyst system. , The result in Figure shows that electron-withdrawing groups accelerate the rate of reaction. One possible reason is that electron-withdrawing substituents reduce the electron density of the −NO 2 group, which makes the reactant easier to be trapped by electron-enriched 1T-MoS 2 under light irradiation.…”
Section: Resultsmentioning
confidence: 96%
“…To further investigate different activities and active sites between 1T/2H-MoS 2 and 2H-MoS 2 , a series of electrochemical measurements were carried out. According to previous researches, the total reaction route to this series of reactions is considered as shown in Scheme . ,, …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the macromolecule compounds function as an inert carrier of metallic active centers, and their special macromolecule effect as well as the interactions with active particles and reaction mass further improves the reactivity of catalysts or selectivity of reaction [17][18][19]. Previous studies show that polyvinylpyrrolidone (PVP)-stabilized noble metals (e.g.…”
Section: Introductionmentioning
confidence: 99%